2014
DOI: 10.1002/lary.24674
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory changes after endoscopic endonasal transsphenoidal approach for skull base tumors

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 18 publications
0
63
1
1
Order By: Relevance
“…However, with the increased number of EETSA procedures, studies concerning the quality of life of patients after EETSA have recently been reported . In our previous studies, olfactory changes increased significantly after EETSA . Of the 413 EETSA patients who underwent EETSA in our clinic, hypernasality was one of the complaints.…”
Section: Introductionmentioning
confidence: 80%
“…However, with the increased number of EETSA procedures, studies concerning the quality of life of patients after EETSA have recently been reported . In our previous studies, olfactory changes increased significantly after EETSA . Of the 413 EETSA patients who underwent EETSA in our clinic, hypernasality was one of the complaints.…”
Section: Introductionmentioning
confidence: 80%
“…Rotenberg, Tam, and Kim described a superior incision that only leaves the most superior 1 cm of the septum (i.e., olfactory cleft). This aggressive harvesting sacrifices a significant amount of olfactory epithelium and may account for their reported decline in olfactory scores.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 19 biopsy specimens that contained olfactory epithelium, 10 had an influx of lymphocytes, macrophages, and eosinophils. Seven of these 10 patients (70%) had an abnormal UPSIT score (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Of the 12 patients with a normosmia (UPSIT score >35), only 3 (25%) had an inflammatory response.…”
Section: Inflammatory Changes To the Olfactory Epithelium In Chronic mentioning
confidence: 96%
“…4,[12][13][14] Addressing olfaction is also important before endoscopic endonasal skull base surgery, because smell loss may occur during tumor resection or harvest of a large nasoseptal flap for reconstruction. [15][16][17][18] In a survey of practicing otolaryngologists, roughly 40% routinely discuss the potential for postoperative anosmia with patients. 11 This figure is important because 17% of malpractice litigation cases from ESS pertain to smell loss or complete anosmia.…”
Section: Introductionmentioning
confidence: 99%